The impact of game engagement and game motivation on game addiction among the young adult multiplayer online battle arena players in Malaysia - Chua, Hung Ming; Goh, Xin Yi; Lim, Zhee Yen (2019)
Playing games have been a way of spending leisure time and releasing stress and also a time to bond with each other. However, in recent years, gaming addiction has made game playing a priority over other activities. Game addiction has been included as a disorder. This study aims to investigate the relationship of game engagement and game motivation on game addiction among young adult Multiplayer Online Battle Arena (MOBA) players in Malaysia. Self-administered survey was distributed online through social media and online forums. A total of 319 participants consisting of young adult MOBA players in Malaysia from 18 to 35 years old participated in this study. The survey includes demographic data, Game Engagement Questionnaire (GEQ), Gaming Motivation Scale (GAMS) and Internet Gaming Disorder Scale – Short-Form (IGDS9-SF). Results from correlation showed that game engagement and all six subscales of game motivation: intrinsic motivation, integrated regulation, identified regulation, introjected regulation, external regulation and amotivation were significantly correlated to game addiction. Result from the multiple regression showed that game engagement, integrated regulation, introjected regulation and amotivation significantly predicted game addiction. The outcome of the factors, such as game engagement, integrated regulation, introjected regulation and amotivation, in predicting game addiction can be explored in future researches. The outcome of this study can give awareness to the young adults and general public regarding their gaming behaviors. Alternative prevention and intervention can be done based on the variables studied in relation to game addiction.